Foundation HTML5 Animation with JavaScript - Lamberta, Billy; SpringerLink (Online service) (Berkeley, CA : Apress, 2011)
Foundation HTML5 Animation with JavaScript covers everything that you need to know to create dynamic scripted animation using the HTML5 canvas. It provides information on all the relevant math you'll need, before moving on to physics concepts like acceleration, velocity, easing, springs, collision detection, conservation of momentum, 3D, and forward and inverse kinematics. Foundation HTML5 Animation with JavaScript is a fantastic resource for all web developers working in HTML5 or switching over from Flash to create standards-compliant games, applications, and animations that will work across all modern browsers and most mobile devices, including iPhones, iPads, and Android devices. You will learn how to utilize the amazing animation and physics-based code originally created by author Keith Peters in his hugely successful Foundation ActionScript Animation in all of your HTML5 applications. In no time at all, you'll understand the concepts behind scripted animation and also have the ability to create all manner of exciting animations and games.
Keywords: Computer science; Computer Science; Computer Science, general